280 Is blue-enriched light more effective than red light to enhance vigilance and cognitive performance in Parkinson's Disease?. (3rd May 2021) - Rosinvil, Thaïna; Daneault, Veronique; Vanderwalle, Gilles; Desaultels, Alex; Forcier, Pierre; Gaudet-Fex, Benjamin; Apinis-Deshaies, Amélie; Aumont, Tomy; Constantin, Ioana Medeleine; Matute, Andrea; Gagnon, Jean-Francois; Gosselin, Nadia; et al.
Abstract: Introduction: Approximately 50% (between 16–74%) of adults with Parkinson's disease (PD) show excessive daytime sleepiness. Besides its important role for vision, light conveys a powerful stimulating signal for alertness and cognition. Recent research has demonstrated that the blue part of light spectrum is the most efficient in enhancing vigilance and cognitive performance in young and older healthy individuals, thanks to a specific photoreception system within the eye which is particularly sensitive to blue wavelength. The aim of this pilot study was to compare the effects of blue-enriched light exposure (BL) and red-light placebo exposure (RL) on psychomotor vigilance and cognitive performance in adults with PD. Methods: Sixteen participants with idiopathic PD (64.0±5.5 yrs, 6 women, Hoehn and Yahr status: 2) completed a brief neuropsychological assessment to exclude dementia, self-reported questionnaires and a complete eye examination in screening visits. The one-day experimental procedure included 1.25 h period of baseline dim-light exposition, followed by two light conditions presented in a counterbalanced design and separated by 15 minutes in dim-light: 1.25 h of BL at 959lux and 1.25 h of placebo RL condition at 472lux. Both light conditions were delivered by Luminette®. Data were normalized according to baseline dim-light evaluation. Mixed analyses of variance (2 light conditions X 2 orders) were performed to compare performance on an auditory psychomotor vigilance task (A-PVT) and an auditory 2-back cognitive tasks (A-2-back) during light exposure. Results: We observed no significant effect of light conditions, orders and no interaction on reaction time (RT) and number of correct answers for the A-2-Back task. Furthermore, there was no significant difference between BL and RL on A-PVT performance including median RT, shift in optimum RT (i.e., mean RT from fastest 10% RT), and duration of response in the lapse domain (i.e., mean RT from slowest 10% RT). Conclusion: These preliminary results do not support the notion that blue-enriched white light exposure is more efficient than red light exposure to stimulate psychomotor vigilance and cognitive performance in adults with PD. Next steps of analyses will compare the effects of BL and RL on subjective sleepiness and EEG cortical activation in the same population. Support (if any): CIHC & QPN